The Influence of Online Gaming on the Learning Outcomes of Grade V Students at UPT SD Negeri 064025 Flamboyan Raya - Ruth Kesia Simatupang; Patri Janson Silaban; Regina Sipayung; Rumiris Lumban Gaol (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This research aims to determine whether there is an influence of online games on the learning outcomes of class V students at UPT SD Negeri 064025 Flamboyan Raya Medan for the 2022/2023 academic year. The population is all class V students at UPT SD Negeri 064025 Flamboyan Raya Medan, totaling 158 students. Sampling used purposive sampling and the sample used was class V-D, totaling 28 students at UPT SD Negeri 064025 for the 2022/2023 academic year. The method used in this research is a quantitative survey type research method. The survey type quantitative research method used in this research was to find the effect of playing online games on the learning outcomes of class V students at UPT SD Negeri 064025 Flamboyan Raya Medan. Based on the results of statistical processing, it shows that the level of addiction to playing online games among students is included in the strong category with an average of 88.28. Meanwhile, student learning outcomes have not met the KKM that has been implemented with an average of 72.85. By using the test tcount = 4,530 while ttable = 2,056 because tcount ≥ ttable then Ho is rejected and Ha is accepted. This proves that there is a significant influence between playing online games on the learning outcomes of class V students at UPT SD Negeri 064025 Medan Selayang for the 2022/2023 academic year.